Prospective Stratégique : Elaboration de Scénarios sur la Transition Agroécologique (TAE) en Tunisie / Rappel de Quelques Eléments d’Orientations Méthodologiques - Sghaier, Mongi; Frija, Aymen; Darghouth, Mohamed Aziz (International Center for Agricultural Research in the Dry Areas, 2024)
This methodological brief delineates the strategic foresight process through eight key steps: i) identification of the central question for exploring future scenarios; ii) identification of key influencing factors related to the question; iii) identification of key external driving forces; iv) ranking these forces according to importance and unpredictability; v) development of a scenario logic with two main axes of critical forces; vi) Concretizing the scenarios narratives in a more explicit way; vii) explore the implications of these scenarios on food systems outcomes ; and finally viii) selection of advanced indicators to monitor and refine the scenarios over time. The document briefly defines and presents each of these methodological steps.